Relationship between Vitamin B9 (Folic Acid), Vitamin B12 (Cobalamin), and Peripheral Neuropathy in Children with Beta-Thalassemia Major - Uni Gamayani; Titin Junaidi; Nushrotul Lailiyya; Nur Suryawan; Nanan Sekarwana (Global Medical & Health Communication (GMHC), 2021)
Vitamin B9 (folic acid) and B12 (cobalamin) are essential vitamins that play roles in the process of hematopoiesis and maintaining the function of peripheral nerves. Therefore, these deficiencies may create a risk for peripheral neuropathy in beta-thalassemia major patients. The purpose of this study is to determine the relationship between vitamin B9 level, vitamin B12 level, and peripheral neuropathy in beta-thalassemia major children. It was an observational analytical study with a case-control design has been conducted at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, in May–July 2019. There were 47 beta-thalassemia major children with peripheral neuropathy (case) and 41 healthy children (control). All subjects completed a general demographic questionnaire, underwent neurological examination, and were tested for vitamin B9 and B12 serum levels. Data were then analyzed using the unpaired t test to compare the vitamin levels between both groups and Spearman’s rank correlation test to investigate the correlation between vitamin levels and the number of affected nerves in the case group. Comparison of folic acid levels in the case group (21.52±6.22 ng/mL) and the control group (23.81±7.51 ng/mL) showed no significant difference (p=0.19). In contrast, cobalamin in the case group (288.57±168.61 ng/mL) and the control group (385.95±197.48 ng/mL) showed a significant difference (p=0.01). In addition, there was a moderate correlation (p=0.004, r=0.41) between folic acid level and the number of motoric nerves affected in the case group. In conclusion, cobalamin level correlates with peripheral neuropathy in beta-thalassemia major patients, and folic acid level correlates with the number of affected nerves, especially motoric nerves. HUBUNGAN ANTARA VITAMIN B9 (ASAM FOLAT), VITAMIN B12 (KOBALAMIN), DAN NEUROPATI PERIFER PADA ANAK DENGAN TALASEMIA BETA MAYORVitamin B9 (asam folat) dan B12 (kobalamin) merupakan vitamin esensial yang berperan dalam proses hematopoesis dan menjaga fungsi saraf tepi. Defisiensi vitamin ini dapat menimbulkan risiko neuropati perifer pada pasien talasemia beta mayor. Tujuan penelitian ini mengetahui hubungan antara kadar vitamin B9, vitamin B12, dan neuropati perifer pada anak talasemia beta mayor. Metode penelitian ini adalah analitik observasional dengan rancangan studi kasus kontrol yang dilakukan di RSUP Dr. Hasan Sadikin Bandung, Indonesia pada Mei–Juli 2019. Terdapat 47 anak talasemia beta mayor dengan neuropati perifer (kelompok kasus) dan 41 anak sehat (kelompok kontrol). Seluruh subjek penelitian mengisi kuesioner demografi umum, menjalani pemeriksaan fisis neurologis, serta dilakukan tes kadar vitamin B9 dan B12 serum. Uji t test tidak berpasangan digunakan untuk membandingkan kadar vitamin pada kedua kelompok dan uji korelasi Spearman untuk membandingkan kadar kedua vitamin tersebut dengan jumlah saraf yang terkena pada kelompok kasus. Perbandingan kadar asam folat kelompok kasus (21,52±6,22 ng/mL) dengan kelompok kontrol (23,81±7,51 ng/mL) menunjukkan perbedaan yang tidak bermakna (p=0,19), sedangkan perbandingan kadar kobalamin kelompok kasus (288,57±168,61 ng/mL) dengan kelompok kontrol (385,95±197,48 ng/mL) menunjukkan perbedaan yang bermakna (p=0,01). Selain itu, terdapat korelasi sedang (p=0,004; r=0,41) antara kadar asam folat dan jumlah saraf motorik yang terkena pada kelompok kasus. Kesimpulan, kadar kobalamin berhubungan dengan neuropati perifer pada penderita talasemia beta mayor dan kadar asam folat berhubungan dengan jumlah saraf yang terkena, terutama saraf motorik.